To study the association of high sensitivity C-reactive protein with metabolic syndrome - Saini, Vinod; Gupta, Abhishek; Arora, Mayank; Virmani, S. K. (International Journal of Research in Medical Sciences, 2018)
Background: Metabolic Syndrome is a constellation of dyslipidemia (elevated triglycerides, low high-density lipoproteins (HDL)), elevation of arterial blood pressure (BP), dysregulated glucose homeostasis, and increased abdominal obesity. Methods: We studied the association of high sensitivity C-reactive protein with metabolic syndrome by case-control method in our tertiary care hospital in West U.P. Results: The mean age of cases and controls was 52.6 ± 7.7 and 51.4±7.0 years, respectively. There were 25 (50%) male and 25 (50%) female in case groups, and 27 (54%) males and 23 (46%) females in control group. Our analysis revelaed that there was a significant association between hs-CRP and the central obesity when compared in case-control group (3.57 vs 0.96 mg/L) (p value <0.001). There was no significant association between hs-CRP and high triglycerides, hypertension, diabetes, and reduced high density lipoprotein cholesterol. Conclusions: Raised hsCRP level can be considered as a surrogate marker of chronic inflammation in patients with metabolic syndrome.